IDENTIFICATION OF INSECT SPESIES ASSOCIATED WITH AVOCADO SEEDS (Persea americana Mill) - Dewi Mellaninyanto; Orbanus Naharia; Utari Satiman (Universitas Negeri Manado, 2022)
Avocado (Persea americana Mill) is a fruit plant that has high nutritional value and is relatively economical. Efforts to increase the production of avocado seeds (Persea americana Mill) are still often constrained by pests and diseases. This study aims to determine the types of insects associated with avocado seeds (Persea americana Mill) and the level of damage to avocado seeds (Persea americana Mill) due to insect pests in Seeds Garden of the Melati Women Farmer Group 2, Ranowulu District, Bitung City. This study used a survey method, namely direct observation (visual) of pests that attack avocado seeds (Persea americana Mill). This research is a descriptive research with survey method. Observation activities by direct observation on avocado plant seeds (Persea americana Mill). Insects were identified using an insect identification book guide. The results of identification and direct observation at the Seeds Garden of the Melati Women Farmers Group 2, Ranowulu District, Bitung City, found 3 orders consisting of 4 insects, namely the Ordo Orthoptera Wood Grasshopper (Valanga nigricornis) and Green Steamed Grasshopper (Atractomorpha crenulata), Ordo Homoptera White Dompolan Tick (Planococcus citri), Ordo Hemiptera Bapak Pucung (Dysdercus cingulatus). The results showed that the percentage of seeds attacked by insect pests in the Seeds Garden of the Melati Women Farmer Group 2, Ranowulu District, Bitung City with a seedling age of 1-10 months was 36.66% and a damage rate of 26.97% of the total seeds of the 30 seeds that had been observed and included in the moderately damaged category.